Plasticity in the central nervous system: do synapses divide? - Carlin, R K (1983)
Changes in the proportion of synapses containing postsynaptic densities with perforations during periods of increased synapse formation have led us to propose a hypothesis describing a possible division of preexisting synapses. Relevant features of this model are that various types of stimulation result in the following sequence of events: (i) the synaptic junction increases in area; (ii) a perforation forms in the enlarging synaptic junction; (iii) a synaptic spinule appears apposed to the perforation in the postsynaptic density; (iv) the perforation in the synaptic junction increases in size until the synaptic junction splits into two separate synaptic junctions within the same synaptic terminal; and (v) the dendritic spine divides into two, each containing a synaptic junction. Physiological responses in which synapse division may possibly play a role include hormone-induced neuronal changes, reinnervation of dendrites after lesions, and learning and memory.